Formulaic sequences for improving oral fluency - Oberg, Kristopher (My University, 2013)
In the English as a second language (ESL) and English as a foreign language (EFL) classroom, the focus is often on teaching reading, writing and grammar skills while little time is spent teaching speaking skills. This becomes a problem when students need to use English to speak. Many adult nonnative English language learners studying abroad in English speaking countries need an extended time immersed in the language before they are comfortable or even able to communicate with the spoken word effectively. This is not desired by the language learners, and it is not necessary to send these language learners out into the world ill equipped. Oral fluency can be taught and the indivisible multiword language chunks, known as formulaic sequences, are one way to accomplish this goal. This paper addresses this issue by first defining what fluency is and then by identifying, defining and applying teachable communication features to improve oral fluency. The body of this paper compiles the research of many scholars in the fields of oral fluency, formulaic sequences and speech communities. Each one of these fields helps to identify and explain effective approaches and tools for improving English language learners' oral fluency. Combining how oral fluency is understood, what oral communication consists of and where oral communication takes place leads to a greater understanding of how to teach speaking skills. This paper then concludes with a Unit Plan containing four lessons that utilize the above research for practical classroom application. The information in this paper can be applied to create an effective curriculum framework for teaching speaking skills in the ESL/EFL classroom.
Plan B Paper. 2013. Master of Arts-TESOL--University of Wisconsin-River Falls. English Department. 94 leaves. Includes bibliographical references (leaves 83-85).
Keywords: Formulaic sequences; Fluency (Language learning); Speaking skills; Oral-formulaic analysis; English language--Study and teaching--Foreign speakers; English language--Pronunciation by foreign speakers; Oral communication; Oral fluency; TESOL